The Influence of Motivation, Zakat Knowledge, and Attitude on the Amount of Zakat Al Maal Paid Online via Bank Jago Syariah - Ramadhan, Noufal; Muljaningsih, Sri (Islamic Economics and finance in Focus, 2025)
Technological developments in the digital age have made it easier for Muslims to fulfill their zakat obligations. However, research specifically discussing the amount of online zakat maal payments, particularly through Bank Jago Syariah, is still limited. The purpose of this study is to analyze the influence of motivation, knowledge about zakat, and attitude on the amount of online zakat maal payments at Bank Jago Syariah. The approach used is quantitative associative with a survey method through the distribution of questionnaires to 130 respondents who have made online zakat maal payments through the Bank Jago Syariah application. The sampling technique used purposive sampling, while data analysis in this study was conducted using the Partial Least Square–Structural Equation Modeling (PLS-SEM) model through SmartPLS software. The results of the study indicate that motivation, zakat knowledge, and attitude have a positive and significant effect on the amount of online zakat maal payments. These findings show that the higher the motivation, level of zakat knowledge, and positive attitude of individuals, the greater their tendency to increase the amount of zakat maal payments through the Bank Jago Syariah digital platform.